Effects of different factors on the flux in the PAHA fouling experiment of forward osmosis membrane processes - Deng, Anqi (2009)
Forward osmosis (FO) membrane is a type of membrane driven by osmotic pressure difference, which owns the benefit of low cost and energy consumption. However, the internal concentration polarization effect reduces the effective osmotic pressure difference across the active layer of FO membrane, which induces a low-than-expect flux value. Besides, as a common problem that existed in the water treatment field by using membrane technology, fouling problem, mainly cake layer formation, also significantly affects the flux performance in the FO processes. Humic Acid is kind of a ubiquitous substance existing in natural waters. The study of fouling problem caused by the humic acid is important in the proper use of forward osmosis. The fouling condition is mostly affected by the combination effect of various factors, including the feed solution concentration, pH value, hydrodynamic conditions, and chemical binding with the divalent ions and so on. By choosing a proper draw solution type, experiments were conducted to study the effect of different factors on the cake layer formation and the flux performance of FO processes. We concluded that the use of FO membrane under suitable conditions would achieve a better flux performance.